2020
DOI: 10.3390/nano10030418
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effect of Carbon-Based Nanomaterials: In Vitro Study on Stimulation of Inflammasome NLRP3 via Destabilisation of Lysosomes

Abstract: Carbon-based nanomaterials (C-BNM) have recently attracted an increased attention as the materials with potential applications in industry and medicine. Bioresistance and proinflammatory potential of C-BNM is the main obstacle for their medicinal application which was documented in vivo and in vitro. However, there are still limited data especially on graphene derivatives such as graphene platelets (GP). In this work, we compared multi-walled carbon nanotubes (MWCNT) and two different types of pristine GP in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Detailed physicochemical characterization and a full description of the preparation of stock suspensions of GP (250 µg/mL) were stated in our recent work [ 14 ]. The basic characterization is briefly summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Detailed physicochemical characterization and a full description of the preparation of stock suspensions of GP (250 µg/mL) were stated in our recent work [ 14 ]. The basic characterization is briefly summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“… 143 , 144 Recent studies have shown that carbon-based nanomaterials, such as multiwalled carbon nanotubes, can activate the NLRP3 inflammasome through lysosomal destabilization and release of cathepsin B. 145 Nicotine also induces lysosomal membrane permeability in endothelial cells and triggers the lysosomal release of cathepsin B, thus enhancing NLRP3 inflammasome activation. 146 Recent studies have suggested a more generalized function of cathepsin B in the activation of the NLRP3 inflammasome through a direct interaction with NLRP3 at the ER upon stimulation with multiple types of NLRP3 activators, including ATP and nigericin, as well as particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Nanodiamonds have excellent biocompatibility in many different cell lines (in vitro) like HT-29 [ 5 ], macrophages, yeast cells [ 6 ], BHK-21 [ 7 ], MCF-7 [ 8 ]. Prabhakar et al showed no toxicity after incubating MDA-MB-231 (human breast adenocarcinoma) cells with FNDs for 120 h. While other carbon nanomaterials have been reported to cause proinflammatory responses [ 9 ] this is not the case for nanodiamonds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%